The Effects of Active Ageing Promotion Model based on the Concepts of Brain-Based Learning and Challenge-Based Learning among Community Dwelling Older Persons - Bunthan, Winthanyou; Suwathanpornkul, Ittipaat (Journal of Health Sciences and Wellness, 2020)
Abstract This research was quasi-experimental research aimed to study the effect of using the model to promote active ageing, based on the concept of brain-based and challenge-based learning. The sample group was selected from older people in Pa Tan subdistrict, Khun Tan district, Chiang Rai province; 48 persons were divided into 2 groups of 24, as the experimental group and the control group. The research tools included a model to promote active ageing, based on the concept of brain-based and challenge-based learning consisting of 5 stages including the preparation stage, the challenge stage, the understanding stage, the processing new information stage and the conveying information stage. The tools to collect the data were 1) the active ageing test of knowledge and 2) an evaluation of awareness. The data were analyzed by repeated measure MANOVA and Hotelling’s T2 The results showed that the experimental group’s mean score of active ageing knowledge and mean score of active ageing awareness were higher after the experiment than before, with a statistical significance at a level of .05. After the experiment, the experimental group had higher mean scores of active ageing knowledge and active ageing awareness than the control group with a statistical significance of .05.